Seasonal Observations at 79°N Glacier (Greenland) From Remote Sensing and in situ Measurements - Neckel, Niklas; Zeising, Ole; Steinhage, Daniel; Helm, Veit; Humbert, Angelika (Frontiers in Earth Science, 2020)
This study investigates seasonal ice dynamics of Nioghalvfjerdsfjorden or 79$^°$N Glacier, one of the major outlet glaciers of the North East Greenland Ice Stream. Based on remote sensing data and in-situ GPS measurements we show that surface melt water is quickly routed to the ice-bedrock interface with a direct response on ice velocities measured at the surface. From the temporally highly resolved GPS time series we found summer peak velocities of up to 22% faster than their winter baseline. These average out to 9% above winter velocities when relying on temporally lower resolved velocity estimates from TerraSAR-X intensity offset tracking. From our GPS time series we also found short term ice acceleration after the melt season. By utilizing optical satellite imagery and interferometrically derived digital elevation models we were able to link the post melt season speed-up to a rapid lake drainage event (<24 h) with an estimated drainage volume of 28x10⁶ m³. We further highlight that GPS measurements are needed to resolve short term velocity fluctuations with low amplitudes, whereas remote sensing estimates are rather useful for the calculation of general trends in velocity behavior.